The Impact of COVID-19 Policy Measures on European Companies – Empirical Evidence from Belgium, The Netherlands, Denmark and Norway - Heiko Hoppe (Junior Management Science (JUMS), 2022)
This study investigates the economic consequences of COVID-19 policy measures in Belgium, The Netherlands, Denmark and Norway. Using panel data analysis, I examine the effects of various government interventions such as lockdowns or economic support measures on risk-adjusted stock returns of companies in these countries. The findings show that both lockdown-related measures and economic support measures have a positive influence on stock returns. This positive influence is robust against competing effects such as the financial situation of companies and the pandemic itself. This study further finds that the positive influence of policy measures is consistent for companies belonging to sectors that are severely or positively affected by the pandemic. Thereby, this study contributes to the understanding of how COVID-19 policy measures affect companies and closes a research gap by considering these effects in northern European countries. It shows that lockdown-related restrictions have a positive economic impact by hindering the spread of the disease and that economic support measures ease the burden of the pandemic and are thus beneficial.
Keywords: 650; COVID-19; government interventions; financial markets; stock returns; Northern Europe